ANALISIS STRATEGI GURU DALAM MENINGKATKAN BUDAYA LITERASI VISUAL SISWA DI SDN 3 LAKATAN - Padila Zikrila A.Datuamas; Hasia marto; Mustakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Padila Zikrila A. Datuamas D20040040. Analysis of Teacher Strategies in Improving Students’ Visual Literacy Culture at SDN 3 Lakatan. (Supervised by Hasia Marto and Mustakim) The problems in this research are: (1) What strategies are applied by teachers to improve the visual literacy culture of students at SDN 3 Lakatan? and (2) What are the inhibiting factors faced by teachers in enhancing students’ visual literacy culture at SDN 3 Lakatan? The purpose of this study is to identify the strategies used by teachers and the obstacles they encounter in fostering students’ visual literacy culture at SDN 3 Lakatan. This study employed a descriptive qualitative method. Data were collected through observation, interviews, and documentation. The findings reveal that the strategies applied by teachers include experiential learning, direct instruction, indirect instruction, interactive learning, and independent learning. The inhibiting factors consist of limited facilities, time management and classroom control issues, as well as students’ difficulties in understanding the material explained by teachers. In conclusion, teachers utilize appropriate learning tools aligned with the material after analyzing students’ needs prior to teaching. This allows teachers to measure students’ progress in achieving the competencies set in the learning process. The initial step taken by teachers is providing story media or books related to the Independent Curriculum, followed by allocating 10–15 minutes for students to engage in literacy activities.